THE CONCEPT OF SURVIVABILITY OF SATELLITE SYSTEMS,ATTITUDECONTROL AND STABILIZATION - Kulik, A. S.; Luchenko, О. О.; Firsov, S. N. (Radio Electronics, Computer Science, Control, 2012)
The fundamentals of position control and stabilization satellite system survivability assurance based on the principle of selforganization through deep diagnosis accident functional conditions and flexible restorative function are presented.